Analysis Of E-Servqual Dimensions Influencing E-Customer Satisfaction Of My First Media Application Users - Ainani Lukman, Nur; Indrawati, Indrawati (International Journal of Science, Technology & Management, 2024)
The internet's growth in Indonesia has reshaped lifestyles and opened new avenues for businesses. This study examines the impact of e-service quality dimensions on e-customer satisfaction among users of the myFirstMedia application—an innovative digital service ensuring 24/7 customer connectivity. However, there is a noticeable gap between service quality and user expectations. The research, utilizing a quantitative method, combines primary data from Google Forms surveys with secondary data from news articles and previous research. Employing non-probability purposive sampling, the study involves 385 respondents and applies Structural Equation Modeling (SEM) using SmartPLS 4.0 software. Statistical tests reveal that (1) the reliability dimension significantly influences e-customer satisfaction, (2) the responsiveness dimension positively impacts e-customer satisfaction, (3) the security/privacy dimension has a significant positive effect on e-customer satisfaction, (4) the fulfillment dimension significantly contributes to e-customer satisfaction, and (5) the efficiency dimension positively affects e-customer satisfaction. The R-Square coefficient of determination indicates a 52.6% influence of electronic service quality dimensions on e-customer satisfaction. Statistical analysis results confirm the impact of the reliability dimension on e-customer satisfaction. Descriptive analysis highlights that the fulfillment dimension exhibits the lowest percentage value, particularly concerning information on package prices, promotions, and other content within the My First Media application.